The scaling limit of random outerplanar maps - Caraceni, A (Institute Henri Poincaré, 2016)
A planar map is outerplanar if all its vertices belong to the same face. We show that random uniform outerplanar maps with n vertices suitably rescaled by a factor 1/n−−√ converge in the Gromov–Hausdorff sense to 72–√/9 times Aldous’ Brownian tree. The proof uses the bijection of Bonichon, Gavoille and Hanusse (J. Graph Algorithms Appl. 9 (2005) 185–204).